Italian wolves (Canis lupus italicus Altobello, 1921) and molecular detection of taeniids in the Foreste Casentinesi National Park, Northern Italian Apennines. Issue 1 (April 2017) - Poglayen, Giovanni; Gori, Francesca; Morandi, Benedetto; Galuppi, Roberta; Fabbri, Elena; Caniglia, Romolo; Milanesi, Pietro; Galaverni, Marco; Randi, Ettore; Marchesi, Barbara; Deplazes, Peter
Abstract: After centuries of massive decline, the recovery of the wolf ( Canis lupus italicus ) in Italy is a typical conservation success story. To learn more about the possible role of parasites in the wolves' individual and population health and conservation we used non-invasive molecular approaches on fecal samples to identify individual wolves, pack membership, and the taeniids present, some of which are zoonotic. A total of 130 specimens belonging to 54 wolves from eight packs were collected and examined. Taeniid eggs were isolated using a sieving/flotation technique, and the species level was identified by PCR (gene target: 12S rRNA and nad1 ). Taeniid prevalence was 40.7% for Taenia hydatigena, 22.2% for T . krabbei, 1.8% for T. polyachanta and 5.5% for Echinococcus granulosus . The prevalence of E. granulosus is discussed. Our results show that the taeniid fauna found in wolves from the Foreste Casentinesi National Park is comparable to that described for other domestic and wild Italian canids and provides insights into the wolves' diet and their relationship with the environment. Graphical abstract: Highlights: Non-invasive techniques were used to identify individual wolves and their taeniids. The taeniids detected could be linked to individual wolves and to packs. The taeniids detected provided information on the wolves' diet and on zoonotic risk.